2004
DOI: 10.1108/01409170410784301
|View full text |Cite
|
Sign up to set email alerts
|

Safety and customer service: contemporary practices in diversity, organizational development and training and development in the global civil aviation industry

Abstract: The commercial aviation industry is an extremely competitive, safetysensitive high technology service industry. Socio-technical systems, employees and customers must be the arenas of an organization's core competencies. The implications are vast and pervasive affecting no less than the organization's structure, strategy, culture and numerous operational activities. In this article, select findings of a human resource management (HRM) audit are compared to the findings of a review of the literature on diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Research on DEI training in the aviation industry is almost nonexistent. A research study in 2004 took two metrics that airlines are constantly looking at safety and customer service and found that the more training dollars were spent on diversity and other human resources, the better the company fared (Appelbaum, 2004). There is certainly a lot more work to be done in this area.…”
Section: Dei In Aviation and Aviation Educationmentioning
confidence: 99%
“…Research on DEI training in the aviation industry is almost nonexistent. A research study in 2004 took two metrics that airlines are constantly looking at safety and customer service and found that the more training dollars were spent on diversity and other human resources, the better the company fared (Appelbaum, 2004). There is certainly a lot more work to be done in this area.…”
Section: Dei In Aviation and Aviation Educationmentioning
confidence: 99%
“…In the service industries, performing a task without sufficient skill jeopardises service quality, and can degrade and embarrass employees (Smith & Kemmis, 2010). The overwhelming consensus in the literature was that more than any other organization characteristics, an organization's culture was the key to a competitive advantage (Appelbaum & Fewster, 2004).…”
Section: Trainingmentioning
confidence: 99%
“…Because education is a process that develops individuals, gives necessary information, and brings them to certain standards. The prerequisite for the success of the training given in the enterprises is to organize the training according to the needs of the employees (Appelbaum and Fewster, 2004).…”
mentioning
confidence: 99%